2017
DOI: 10.3390/en10121970
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Models for Polymer Free CO2 Foam Fracturing Fluid with the Effect of Surfactant Concentration, Salinity and Shear Rate

Abstract: High quality polymer free CO 2 foam possesses unique properties that make it an ideal fluid for fracturing unconventional shales. In this paper, the viscosity of polymer free fracturing foam and its empirical correlations at high pressure high temperature (HPHT) as a function of surfactant concentration, salinity, and shear rate are presented. Foams were generated using a widely-used surfactant, i.e., alpha olefin sulfonate (AOS) in the presence of brine and a stabilizer at HPHT. Pressurize foam rheometer was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…(4) The foamability and foam stability was higher when the air was used as a gas medium. (5) The foamability of all surfactants increased at high temperature due to Brownian motion in the liquid and enhanced kinematic viscosity leads to better foam generation. However, the foam stability reduced at high temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) The foamability and foam stability was higher when the air was used as a gas medium. (5) The foamability of all surfactants increased at high temperature due to Brownian motion in the liquid and enhanced kinematic viscosity leads to better foam generation. However, the foam stability reduced at high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The foam film is usually stabilized using different surfactants and recently nanoparticles have also been used for this purpose either alone or with surfactants. Foam has different applications in oil and gas industry such as in drilling, hydraulic fracturing, and in enhanced oil recovery (EOR) [2][3][4][5][6]. CO 2 flooding is one of the most commonly used EOR method that involves the injection of compressed CO 2 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The equation governing the viscometric measurements is as follow in Equation (2) [23,44]: The test procedure included the following steps.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Both laboratory and field scale tests have shown that the addition of surfactant increases the gas production by reducing the capillary forces and altering the wettability of shales. The rheology of foam has great importance in fracture treatment design and has been discussed by multitude of studies [8,36,[38][39][40].…”
Section: Foam Fracturing Fluidmentioning
confidence: 99%